System medicine approach to improve diagnosis and prognosis in Autism Spectrum Disorders (ASD), based on extensive genomic, biochemical and clinical data - Asif, M. (2015)
Objectives: The overall objective of the present work is to better understand the biological basis of ASD phenotypic variability and facilitate a fast and accurate ASD diagnosis by seeking behavior associations with specific genetic risk factors for ASD. More specifically the aims are: - ASD data repository and Knowledge base graph: To design and establish a dynamic resource repository for ASD data storage and management; - Behavior Signature for Genetic factors: To associate ASD behavior signatures with genetic data (CNVs and SNV characteristics). Functional genomics data (miRNA, metabolome and neurophysiologic data) will also be included in model definition; - Semantic layer and Enrichment analysis: To enable the integration of a semantic layer to available data. - Predictive models for ASD diagnosis and prognosis: to define predictive models for ASD based on systems biology approaches. - Framework development: To set up a framework – pipeline for analysis of ASD and other related complex diseases.